1996
DOI: 10.4141/cjas96-022
|View full text |Cite
|
Sign up to set email alerts
|

Uterine involution time and ovarian activity in weaned and suckling ewes

Abstract: . Uterine involution time and ovarian activity in weaned and suciling .ro.r. bun. J. Anim. Uterine involution time and ovarian activity were studied in iutumn-and spring-lambiig .*.r. Macroscopic uterine involution was completed earlier in autumn-lambing ewes and this can be related with an earlier resuirption of ovarian endocrine activity. (Call et al. 1976;Schirar and Martinet 1982) did not show any differences. Seasonal differences in uterine involution time have also been reported (Cognie et al. 197 5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 5 publications
6
17
1
1
Order By: Relevance
“…The interval from parturition to first progesterone increase phase in untreated ewes (CE-E1 ewes) was similar to our previous observations (Rubianes et al, 1996), and is within the range reported in other breeds (Mandiki et al, 1990;Wright et al, 1990). However, that value corresponds to a small percentage of ewes, as 24.4% of them did not have luteal progesterone concentrations during the observed period (65 days).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The interval from parturition to first progesterone increase phase in untreated ewes (CE-E1 ewes) was similar to our previous observations (Rubianes et al, 1996), and is within the range reported in other breeds (Mandiki et al, 1990;Wright et al, 1990). However, that value corresponds to a small percentage of ewes, as 24.4% of them did not have luteal progesterone concentrations during the observed period (65 days).…”
Section: Resultssupporting
confidence: 59%
“…Uterine involution is completed by the third week (Rubianes & Ungerfeld, 1993) and the first oestrus is observed ~50 days after parturition (Rubianes et al, 1996) when ewes are maintained in a high nutritional plane. Therefore, as not all ewes are cyclic during early postpartum, for accelerated lambing programmes, oestrus induction managements should be included.…”
Section: Introductionmentioning
confidence: 99%
“…Complete uterine involution is a prerequisite to the maintenance of pregnancy. The time estimated for the completion of uterine involution in sheep varies between 17 and 40 days (Ungerfeld and Sanchez-Davila, 2012;Rubianes et al, 1996;Hauser and Bostedt, 2002). In goat, completion of uterine involution and resumption of sexual activity following parturition depend on several factors, such as nutrition, parity, breed, nursing of offspring and season of parturition (Badawi et al, 2014;Delgadillo et al, 1998 Greyling, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, uterine involution was investigated after slaughter (Van Wyk et al, 1972;Rubianes and Ungerfeld, 1993) or by laparotomy (Rubianes et al, 1996) or using radio-opaque markers (Tian and Noakes, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A normal luteal phase was defined as the presence of progesterone concentrations above 0.5 ng mL -1 for at least 10 d (Rubianes et al 1996). An LH surge was defined as being at least six times higher than basal concentrations.…”
mentioning
confidence: 99%